Dermapen Action on the Skin of White Rats Wistar Strain (Rattus norvegicus) to Evaluate the Efficacy of Avocado Fruit Ethanol Extract Cream (Persea americana Mill.) in Healing Wounds - Suyono, Tan; Mucmaini, Rica; Ginting, Chrismis Novalinda; Pratama, Irza Haicha (Jurnal Penelitian Pendidikan IPA, 2023)
Wounds disrupt anatomical and skin functions. Thus, proper treatment and healing are needed. Saponins, tannins, and flavonoids in natural medicinal extracts accelerate wound healing. Plants and natural substances are usually employed in topical therapy. This study tested the efficacy of ethanol extract cream from the avocado pulp (Persea americana Mill.) in treating dermapen-induced lesions on white rats (Rattus norvegicus) Wistar strain. This is a lab study or an experiment. Mouse samples were divided into four treatment groups of five mice each. This study also found that avocado flesh extract (Persea americana Mill.) significantly improved dermapen scar healing compared to base cream. The treatment groups given avocado pulp extract (Persea americana Mill.) exhibited higher healing percentages than the control group: 60.5, 95.7, 97.3, and 100%. Researchers found that 15% avocado flesh extract cream (Persea americana Mill.) healed dermapen scars best. This study found that avocado flesh extract cream (Persea americana Mill.) accelerates skin regeneration and increases fibroblasts more than base creams. The highest and densest number of fibroblast cells was found in treatment group 3 healing wounds. Fibroblasts indicate active dermapen wound healing.